Amputation Predisposes to Higher Cancer-Specific Mortality Than Limb Salvage Surgery in Pediatric Patients With Osteosarcoma of the Limbs: A Propensity Matching Analysis - Wang, Jinkui; Tang, Jie; Tan, Xiaojun; Zhanghuang, Chenghao; Jin, Liming; Li, Mujie; Zhang, Zhaoxia; Mi, Tao; He, Dawei (Frontiers in Surgery, 2022)
Objective: With the development of osteosarcoma treatment, limb salvage surgery is gradually replacing amputation as the primary surgical option. Should Osteosarcoma of the limbs in children undergo limb salvage surgery? We aimed to use propensity matching analysis test the difference in cancer-specific mortality(CSM) between amputation and limb-salvage surgery in paediatric patients with Osteosarcoma of the limbs. Methods: Patient information was downloaded from the SEER (surveillance, epidemiology, and End Results) database from 2004 to 2018. We included all pediatric osteosarcoma patients who underwent limb salvage or amputation. Multivariate logistic regression models were used to explore the factors influencing patient choice of amputation. Differences in CSM and other causes of mortality(OSM) between limb salvage and amputation were analyzed using cumulative incidence plots and competitive risk regression tests after 1:1 proportional propensity score matching. Results: A total of 1058 pediatric patients with limbs Osteosarcoma were included. Patients who underwent amputations were more likely to be male(OR 1.4, P=0.024) and more likely to have distant metastasis(OR 2.1, P<0.001). Before propensity matching, CSM was 1.4 times higher in patients undergoing amputation than in patients undergoing limb salvage (P =0.017) and 3.4 times higher in OSM (P =0.007). After adjustment for propensity matching, CSM was 1.5 times higher in patients undergoing amputation than in patients undergoing limb salvage (P= 0.028), but there was no significant difference in OSM (HR 3.2, P=0.078). Conclusions: Our results suggested that amputation is associated with a 1.5-fold increase in CSM in pediatric patients with limbs Osteosarcoma. Therefore, in the surgical selection of pediatric patients with Osteosarcoma, limb salvage surgery should be the first choice in the absence of other contraindications.